Analysis of Marketing Public Relations Strategy by. U Provider in Enhancing Brand Awareness Through Social Media - Ochsa Dwiprakasa, Muhammad; Misnawati, Desy; Zinaida, Rahma Santhi; Isnawijayani (Indonesian Scientific Publication, 2025)
This study aims to analyze the marketing public relations strategies the By.U provider employs to increase brand awareness through social media. The research method used is a qualitative approach with several data collection techniques, including interviews, observation, and documentation. The data analysis employed is qualitative data analysis, which involves three main activities: data reduction, data presentation, and conclusion drawing or verification. Based on the research findings, it can be concluded that.U's marketing public relations planning strategy almost entirely adheres to the dimensions and indicators in the strategic planning process outlined by Whalen, known as Whalen’s 7-Step Strategic Planning Process. The only shortcoming lies in the situational analysis dimension, where U did not fully implement a SWOT analysis but only utilised certain aspects. The marketing public relations efforts By.U have generally been successful and aligned with the Three Ways Strategy concept by Thomas L. Harris. However, areas still need improvement, such as the frequency of interaction by the By.U team on Instagram comments, which is rarely done, and the repetitive use of the same color scheme in their posts, leading to follower fatigue. Moreover, there is a lack of broader outreach to less tech-savvy individuals. Additionally, the brand awareness of By.U users and potential users, according to Aaker's (1991) theory, is still at the brand recognition level.